Clinical and magnetic resonance imaging features, and pathological findings of spinal lymphoma in 27 cats - Lorenzo, Valentina; Ribeiro, João; Bernardini, Marco; Mínguez, Juan J.; Moral, Meritxell; Blanco, Carlos; Loncarica, Tina; Gamito, Araceli; Pumarola, Martí (Frontiers in Veterinary Science, 2022)
This multicentric retrospective study describes the clinical and MRI features and pathological studies of spinal lymphoma in 27 cats. MRI characteristics and their possible correlations with histopathological findings were studied. The most frequent neurological signs were rapidly progressive paraparesis (62.9%) or paraplegia (22.2%). Bimodal age distribution was found with 40.7% of cats aged ≤2.5 years (63.6% of them FeLV positive), and 44.4% of cats aged ≥8 years (16.7% of them FeLV positive). Spi-nal lymphoma was generally presented on MRI as an ill-defined epidural focal lesion with moderate to severe spinal cord compression, expanding more than one vertebral body. MRI lesions were typically localized in the lumbar vertebral segment (p=0.01), circumferential to the spinal cord (p=0.04), hyperin-tense on T2-weighted sequences (p= 4.3e-06), and isointense on T1-weighted sequences (p=8.9e-07). The degree and pattern of contrast enhancement were variable. Other morphological patterns included paravertebral masses with extension into the vertebral canal and lesions centered in the spinal nerve roots. Involvement of vertebrae and adjacent spinal soft tissues was present in 74% of cases when pre-sent vertebral involvement was characterized by cortical sparing. When follow-up MRI studies (n=4) were performed after treatment new lesions of similar nature but different localizations and extension were observed. Confirmation of spinal lymphoma was performed by CSF analysis in 4/27 (14.8%) of cases, by FNA in 6/27 (22.2%) of cases, by surgical biopsy in 10/27 (37%) of cases, by FNA and sur-gical biopsy in 1/27 (3.7%) of cases, by CSF, FNA, surgical biopsy and postmorten examination in 1/27 (3.7%) of cases, and postmorten studies in 5/27 (18.5%) of cases. Antemortem diagnosis was achieved in 22/27 (81.5%) cats. The presence of necrosis in histopathological studies as an unfavorable prognostic indicator of survival was significantly more probable when lesions were not hyperintense on T2-weighted sequences (p=0.017). Spinal lymphoma in cats is a complex entity with heterogeneous imaging and histopathological appearance. However, certain MRI features may support a tentative di-agnosis, which in a group of cases can be confirmed when combined with the CSF findings. For the rest of the cases, tissue sampling assisted by imaging findings remains necessary for definitive diagno-sis.